Scorpion Envenomation Among Children: Clinical Manifestations and Outcome (Analysis of 685 Cases) - Bahloul, Mabrouk (The American Society of Tropical Medicine and Hygiene, 2010)
Our objective was to characterize both epidemiologically and clinically manifestations after severe scorpion envenomation and to define simple factors indicative of poor prognosis in children. We performed a retrospective study over 13 years (1990–2002) in the medical intensive care unit (ICU) of a university hospital (Sfax-Tunisia). The diagnosis of scorpion envenomation was based on a history of scorpion sting. The medical records of 685 children aged less than 16 years who were admitted for a scorpion sting were analyzed. There were 558 patients (81.5%) in the grade III group (with cardiogenic shock and/or pulmonary edema or severe neurological manifestation [coma and/or convulsion]) and 127 patients (18.5%) in the grade II group (with systemic manifestations). In this study, 434 patients (63.4%) had a pulmonary edema, and 80 patients had a cardiogenic shock; neurological manifestations were observed in 580 patients (84.7%), 555 patients (81%) developed systemic inflammatory response syndrome (SIRS), and 552 patients (80.6%) developed multi-organ failure. By the end of the stay in the ICU, evolution was marked by the death in 61 patients (8.9%). A multivariate analysis found the following factors to be correlated with a poor outcome: coma with Glasgow coma score ≤ 8/15 (odds ratio [OR] = 1.3), pulmonary edema (OR = 2.3), and cardiogenic shock (OR = 1.7). In addition, a significant association was found between the development of SIRS and heart failure. Moreover, a temperature > 39°C was associated with the presence of pulmonary edema, with a sensitivity at 20.6%, a specificity at 94.4%, and a positive predictive value at 91.7%. Finally, blood sugar levels above 15 mmol/L were significantly associated with a heart failure. In children admitted for severe scorpion envenomation, coma with Glasgow coma score ≤ 8/15, pulmonary edema, and cardiogenic shock were associated with a poor outcome. The presence of SIRS, a temperature > 39°C, and blood sugar levels above 15 mmol/L were associated with heart failure.